2009
DOI: 10.1194/jlr.m800226-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor CAR (NR1I3) regulates serum triglyceride levels under conditions of metabolic stress

Abstract: The nuclear receptor constitutive androstane receptor (CAR) (NR1I3) regulates hepatic genes involved in xenobiotic detoxification as well as genes involved in energy homeostasis. We provide data that extend the role of CAR to regulation of serum triglyceride levels under conditions of metabolic/nutritional stress. The typically high serum triglyceride levels of ob/ob mice were completely normalized when crossed onto a Car 2/2 (mice deficient for the Car gene) genetic background. Moreover, increases in serum tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 30 publications
3
93
2
Order By: Relevance
“…CAR and PXR are also increasingly recognized as important regulators of genes involved in lipid and glucose homeostasis (for review: [70,71]. In particular, CAR activation reduces the expression of critical genes involved in fatty acid oxidation [72], bile acid synthesis and gluconeogenesis [73]. Further studies should evaluate the potential role of these regulations in mediating metabolic disruption by phthalates in light of their potential to activate both PXR and CAR.…”
Section: Discussionmentioning
confidence: 99%
“…CAR and PXR are also increasingly recognized as important regulators of genes involved in lipid and glucose homeostasis (for review: [70,71]. In particular, CAR activation reduces the expression of critical genes involved in fatty acid oxidation [72], bile acid synthesis and gluconeogenesis [73]. Further studies should evaluate the potential role of these regulations in mediating metabolic disruption by phthalates in light of their potential to activate both PXR and CAR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that CAR can be naturally activated under certain disease states. For example, CAR appears to be the regulatory factor that increases serum triglyceride levels in diabetic ob/ob mice as this abnormality becomes normal when the Car Ϫ/Ϫ genotype is introduced into the ob/ob mice (19). NADPH-cytochrome P450 oxidoreductase (POR) transfers electron to reduce cytochrome P450, which is essential for P450 to catalyze the oxygenase reaction.…”
Section: Discussionmentioning
confidence: 99%
“…CAR(Ϫ/Ϫ) mice showed defective basal and inducible expression of xenobiotic enzymes and altered responses to drugs (Wei et al, 2000). CAR has been suggested recently to play a role in energy metabolism, ranging from thyroid hormone metabolism (Maglich et al, 2004;Qatanani et al, 2005) to lipogenesis (Roth et al, 2008a,b;Gao et al, 2009;Maglich et al, 2009), gluconeogenesis (Ueda et al, 2002;Kodama et al, 2004;Miao et al, 2006;Gao et al, 2009;Wada et al, 2009), and obesity and diabetes (Dong et al, 2009;Gao et al, 2009). It is unclear whether the effect of CAR on lipogenesis involves the cross-talk with LXRs.…”
Section: Introductionmentioning
confidence: 99%